ANDRI HOLISTIC-INTEGRATIVE INDONESIAN LANGUAGE LEARNING AS A FOUNDATION FOR EARLY CHILDHOOD LITERACY: HOLISTIC-INTEGRATIVE INDONESIAN LANGUAGE LEARNING AS A FOUNDATION FOR EARLY CHILDHOOD LITERACY - Andri Hardiyana; Nur Syamsiyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
Early childhood Indonesian language learning is an important foundation for sustainable literacy development. The integrative holistic approach emphasizes the integration of aspects of child development, language, cognition, social-emotional, moral, and motor skills into a single meaningful learning process. This study aims to describe the implementation of holistic integrative Indonesian language learning and analyze its contribution to strengthening the literacy foundation of early childhood. This study uses a descriptive qualitative method with teachers and children at RA Alwaqiah, Cirebon City, as subjects. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis techniques were data condensation, data presentation, and conclusions. The results showed that the achievements of the implementation of the five main components of holistic integrative Indonesian language learning were a) integration of language with cognitive (85%), b) integration of language with social-emotional (80%). c) integration of language with motor skills (75%). d) collaboration between schools/teachers and parents (88%). e) literacy environment (90%). Language learning designed through activities such as playing, storytelling, singing, dialoguing, and integrated environmental literacy can improve children's listening and speaking skills as well as their readiness for early reading and writing. In addition, the integrative holistic approach encourages active child involvement, enriches vocabulary, and builds an interest in reading from an early age. Thus, integrative holistic Indonesian language learning has proven to be an effective strategy in building a comprehensive and sustainable foundation for early childhood literacy.